Social criteria as a component of the evaluation system of investment projects for reconstruction and restoration of housing destroyed as a result of russian aggression - Fisunenko , P; Popovychenko , I.; Kuzmin , T. (Ways to Improve Construction Efficiency, 2023)
The article examines the importance of social criteria as an important component of the evaluation system of investment projects aimed at the reconstruction and restoration of housing stock destroyed as a result of Russia's armed aggression against Ukraine. In the context of large-scale destruction of infrastructure and housing in a significant territory of the country, the problem of effective, targeted and socially oriented restoration appears as one of the key challenges for the state, local communities and international partners. Attention is focused on the need to expand the system of evaluation of investment projects by including social criteria that reflect not only the technical and economic feasibility of restoration, but also the social significance and effectiveness of the implementation of such projects for the affected population. The main groups of social criteria were identified, including: the level of housing provision for vulnerable categories of the population, integration of internally displaced persons into local communities, ensuring access to basic social services, development of local infrastructure, safety of the living environment, preservation of social ties and identity of communities. It was emphasized that the introduction of such criteria into the assessment allows for a more equitable distribution of resources, taking into account the real needs of residents, increasing the level of social stability of regions and reducing the risks of repeated population displacement. Methodological approaches to the integration of social indicators into the general assessment system are also described, in particular the use of multi-criteria analysis, expert assessment and social monitoring. The conclusion was made about the need to develop unified national standards for assessing reconstruction investment projects taking into account the social component, which will increase transparency and trust in the reconstruction process on the part of citizens, investors and the international community.